1980
DOI: 10.1111/j.1834-7819.1980.tb03705.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional odontodysplasia

Abstract: A case of regional odontodysplasia is reported. An unusual feature, only twice previously described in the world literature of fifty-four cases, was the presence of an apparently normal tooth within the group of affectd teeth. The implications of such a finding for the various theories relating to aetiology and pathogenesis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The main question is whether to remove the affected teeth or not, but we believe that this decision should be taken after the assessment of each individual case of RO. Some authors prefer extraction and replacement with removable, and later, fixed prostheses [3,5,10,13,44,45], while others have suggested keeping the unerupted teeth, and waiting for their calcification and hoped for eruption [1,3,13,36]. When the affected unerupted teeth are retained, some authors have suggested that a removable temporary prosthesis may be constructed over them during the period of skeletal growth in order to preserve the alveolar ridge [12,51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main question is whether to remove the affected teeth or not, but we believe that this decision should be taken after the assessment of each individual case of RO. Some authors prefer extraction and replacement with removable, and later, fixed prostheses [3,5,10,13,44,45], while others have suggested keeping the unerupted teeth, and waiting for their calcification and hoped for eruption [1,3,13,36]. When the affected unerupted teeth are retained, some authors have suggested that a removable temporary prosthesis may be constructed over them during the period of skeletal growth in order to preserve the alveolar ridge [12,51].…”
Section: Discussionmentioning
confidence: 99%
“…When the affected teeth erupt, RO can be misdiagnosed as dental caries, and therefore, the teeth will be extracted without being submitted for histological examination [12]. Many cases of RO are also misdiagnosed as malformed teeth or odontomes [44,45].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued, however, that a single act of damage would have to occur in utero and it is difficult to envisage such damage extending from the deciduous to the permanent dentition, with the occasional tooth in a quadrant remaining unaffected. 16 Activation of a latent virus in the odontogenic epithelium has also been suggested as a cause for the disorder, 7,17,18 but no virus particles have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…19 A hereditary factor can be discounted because of the lack of evidence of such a history in cases reported to date. The possibility of maternal illness, drug therapy, or both as etiologic factors was suggested by cases reported in children whose mothers had pneumonia 14 or toxemia 16 during pregnancy or who took diuretics, 20 tranquilizers, or hormones during the first trimester.…”
Section: Conflicts Of Interestmentioning
confidence: 99%